INOVASI DAN MASA DEPAN PENDIDIKAN DIGITAL - Halimatus Sadiyah; Siti Roudhoh; Mardiah; Nilawati Tadjudin; Andi Warisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of Generative Artificial Intelligence (AI) has significantly transformed digital education by creating both opportunities and challenges for the learning process. This study aims to examine the opportunities, risks, and implications of Generative AI for the future of education through a Systematic Literature Review (SLR) approach. The data were collected from scholarly articles, academic books, reports from international organizations, and reputable publications published between 2019 and 2025. Data analysis was conducted using content analysis to identify major themes related to the implementation of Generative AI in digital education. The findings reveal that Generative AI offers numerous benefits, including supporting personalized learning, improving access to educational resources, enhancing student engagement, assisting educators’ professional tasks, and fostering the development of twenty-first-century skills. However, the technology also presents several challenges, such as plagiarism, academic integrity violations, technological dependency, misinformation, and issues related to ethics and data privacy. The study highlights that the successful implementation of Generative AI requires stronger digital literacy, adaptive educational policies, and effective collaboration between human intelligence and artificial intelligence. When properly managed, Generative AI has the potential to become a catalyst for a more innovative, inclusive, and sustainable educational transformation in the future.